History of Islamization of the Cikondang Traditional Village Community in Pangalengan - Supendi, Usman; Juniawan, Hendro Kartika; Savitri, Alfa Dini; Anugerah, Rizpat (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This article discusses the process of Islamization of the Cikondang Village indigenous community and the social changes that occurred within it. This research aims to (1) determine the historical process of the formation of the Cikondang Traditional Village, (2) determine the development process of Islamization that occurred among the Cikondang Traditional Village community, (3) determine the social, economic, and political structure of the Cikondang Traditional Village community. This research method is a historical method with stages (1) Heuristics, (2) Criticism, (3) Interpretation and (4) Historiography. The results of this research are that historically the Cikondang Traditional Village community has been established for 400 years since their ancestors, Pameget Uyut and Wife Uyut established settlements around the current Lamajang Village. The Islamization process that took place in the Cikondang Traditional Village took place sporadically through a cultural and traditional approach as well as a philosophy that was accepted by the community at that time. In the next stage, a system was formed that continued to undergo adjustments, in the social, economic and political sectors until now.